Macrophage metabolism in inflammatory heart disease: new insights and therapeutic implications - Xiang, Aocheng; Chang, Aie; Zhou, Jichang; Jin, Jin; Zhang, Xi; Wang, Qianyan (Frontiers in Medicine, 2025)
Macrophages are essential immune cells involved in pathogen clearance, initiation and resolution of inflammation, and tissue repair across multiple organ systems. They exhibit remarkable phenotypic diversity, encompassing classical M1 and M2 subtypes-further subdivided into M2a, M2b, M2c, and M2d-as well as newly identified subsets such as Mreg, M4, Mox, and Mhem, each with distinct functional roles. Emerging evidence highlights cellular metabolism as a central regulator of macrophage phenotype and function. Distinct metabolic programs underpin the polarization of M1 and M2 macrophages in response to environmental cues, thereby critically influencing disease progression and tissue outcomes. Cardiovascular disease remains a leading cause of morbidity and mortality worldwide. In the heart, macrophages represent a dominant immune cell population and play integral roles in both pathological injury and tissue regeneration. This review provides a comprehensive overview of macrophage ontogeny, phenotypic heterogeneity, and metabolic reprogramming, with a particular focus on their roles in inflammatory heart diseases. We synthesize current findings on how metabolic pathways shape macrophage behavior and function within the cardiac microenvironment and discuss the therapeutic potential of targeting macrophage metabolism to modulate inflammation, promote repair, and improve clinical outcomes in cardiovascular disease.